2020
DOI: 10.21037/atm-20-3307
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of glucocorticoids to treat COVID-19: a rapid review and meta-analysis

Abstract: Background: Glucocorticoids are widely used in the treatment of various pulmonary inflammatory diseases, but they are also often accompanied by significant adverse reactions. Published guidelines point out that low dose and short duration systemic glucocorticoid therapy may be considered for patients with rapidly progressing coronavirus disease 2019 (COVID-19) while the evidence is still limited.Methods: We comprehensively searched electronic databases and supplemented the screening by conducting a manual sear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 47 publications
0
53
0
1
Order By: Relevance
“…Use of corticosteroid treatment was found to be associated with higher mortality (RR 2.11; 95%CI 1.13 to 3.94) in nCOV-2019 and SARS patients in a meta-analysis of 15 studies conducted by Yang et al, 68 while three meta-analyses found that corticosteroid use did not worsen/improve mortality in patients with nCOV-2019, SARS-Cov and MERS-Cov. [69][70][71] Further, the meta-analysis by Li et al 70 also observed a delayed time to virus clearance in the corticosteroid group compared to controls (MD 3.78; 95%CI 1.16 to 6.41). The findings of our meta-analysis are also in line with the previously published meta-analyses on corticosteroids.…”
Section: F I G U R Ementioning
confidence: 93%
“…Use of corticosteroid treatment was found to be associated with higher mortality (RR 2.11; 95%CI 1.13 to 3.94) in nCOV-2019 and SARS patients in a meta-analysis of 15 studies conducted by Yang et al, 68 while three meta-analyses found that corticosteroid use did not worsen/improve mortality in patients with nCOV-2019, SARS-Cov and MERS-Cov. [69][70][71] Further, the meta-analysis by Li et al 70 also observed a delayed time to virus clearance in the corticosteroid group compared to controls (MD 3.78; 95%CI 1.16 to 6.41). The findings of our meta-analysis are also in line with the previously published meta-analyses on corticosteroids.…”
Section: F I G U R Ementioning
confidence: 93%
“…While most patients with mild disease develop an appropriate immune response that culminates with viral clearance 3 , severe disease manifestations have been linked to lymphopenia and immune hyperresponsiveness leading to cytokine release syndrome (CRS) 1,2,4,5 . The most effective therapeutic approaches developed so far for severe cases involve either general immunosuppression with glucocorticoids 6 or selective neutralization of interleukin 6 (IL-6) with tocilizumab 7 , a monoclonal antibody used to manage CRS in indications such as rheumatoid arthritis 8 . The efficacy of these therapies strongly support a key role for immune dysregulation in the pathogenesis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the literature uncovered 3 articles examining the role of corticosteroids in patients with COVID-19. In a meta-analysis of systemic corticosteroid use in COVID-19 patients by Lu et al [22], the pooled results from 5 cohort studies found that corticosteroids did not reduce the risk of mortality (relative risk (RR) = 2.0, 95% CI: 0.7-5.8, I 2 = 90.9%), shorten the duration of pneumonia (weighted mean difference (WMD) = − 1.0 day, 95% CI: − 2.9 -0.9), or shorten hospital stay (WMD = 2.4 days, 95% CI: 1.4-3.4, I 2 = 0.0%) in COVID-19 patients. However, the duration of fever was significantly lower in COVID-19 patients who received corticosteroids than patients who did not receive corticosteroids (WMD = − 3.2 days, 95% CI: − 3.6 to − 2.9).…”
Section: Systemic Corticosteroids (Against Routine Use)mentioning
confidence: 99%